Isolation and characterisation of phages targeting clinical Pseudomonas aeruginosa carrying virulence genes - Jamil, NAB; Baqer, AA; Hussin, A; Nor, NSM; Siti Noor Adnalizawati Adnan (Malaysian Soc Microbiology, 2024)
Indexed by WOS/SCOPUS